2016
DOI: 10.4236/psych.2016.711136
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Self-Esteem among Middle School Students in Japan, 1989-2002

Abstract: This paper examined temporal changes in self-esteem among middle school students in Japan from 1989 to 2002. Previous research showed that self-esteem decreased among middle school students between 1999 and 2006. However, it was unclear whether such a decrease was also present in other periods of time. To obtain a better understanding of how people adapt to socio-economic environments, it is important to gain a more comprehensive view of such long-term cultural/social changes. Therefore, to supplement the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…In the U.S., it increased over time (e.g., Twenge and Campbell, 2001 ; Gentile et al, 2010 ). In contrast, in Japan, it decreased (Oshio et al, 2014 ; Ogihara, 2016c ; Ogihara et al, 2016 ) 6 .…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., it increased over time (e.g., Twenge and Campbell, 2001 ; Gentile et al, 2010 ). In contrast, in Japan, it decreased (Oshio et al, 2014 ; Ogihara, 2016c ; Ogihara et al, 2016 ) 6 .…”
Section: Future Directionsmentioning
confidence: 99%
“…This phenomenon in Japan is intriguing and thought-provoking because, at a first glance, it seems paradoxical. Specifically, considering that Japanese culture has become more individualistic, it would be expected that self-esteem has increased, but it has actually decreased (for a more detailed discussion, see Ogihara, 2016c ; Ogihara et al, 2016 ). Why has self-esteem decreased rather than increasing in Japan?…”
Section: Future Directionsmentioning
confidence: 99%
“…Naturally, the developmental pattern is different because the time periods covered in the surveys are significantly different ( Tables 1, 2). Moreover, previous research has shown that the average levels of self-esteem decreased over time in Japan [ (23)(24)(25); for a review of historical changes in self-esteem in Japan see Ogihara (26)]. Thus, the self-esteem score should not be simply averaged across the surveys that were conducted over nine years.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the absence of a drop in self-esteem in Japan might be caused by the cohort effect. Specifically, older cohorts might have higher self-esteem and younger cohorts might have lower self-esteem ( 23 26 ), which might obscure the drop of self-esteem in Japan. Thus, in the future, it is necessary to analyze longitudinal data which can distinguish between age differences and cohort differences.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-temporal meta-analyses of Rosenberg's self-esteem reveal a declining trend in both China (Liu & Xin, 2015;Xin, Niu, & Chi, 2012) and Japan (Oshio, Okada, Mogaki, Namikawa, & Wakita, 2014). Ogihara and his colleagues (Ogihara, 2016;Ogihara, Uchida, & Kusumi, 2016) also found declining self-esteem over time in surveys of Japanese students and young adults.…”
Section: Usamentioning
confidence: 90%